A Rising Natural Rate of Unemployment: Transitory or Permanent? - Mary Daly; Bart Hobijn; Aysegul Sahin; Robert Valletta (Tinbergen Institute, 2011)
The U.S. unemployment rate has remained stubbornly high since the 2007-2009 recessionleading many to conclude that structural, rather than cyclical, factors are to blame. Relying on astandard job search and matching framework and empirical evidence from a wide array of labormarket indicators, we examine whether the natural rate of unemployment has increased since therecession began, and if so, whether the underlying causes are transitory or persistent. Our analysessuggest that the natural rate has risen over the past several years, with our preferred estimateimplying an increase from its pre-recession level of close to a percentage point. An assessment ofthe underlying factors responsible for this increase, including labor market mismatch, extendedunemployment benefits, and uncertainty about overall economic conditions, implies that only asmall fraction of this increase is likely to be persistent.
urn:NBN:nl:ui:31-1871/38556
Keywords: E24; J3; J6; 330; equilibrium unemployment; Beveridge curve; structural unemployment; mismatch